Infinite Judgements and Transcendental Logic - Longo, Anna; Collier, Madeleine; Erkan, Ekin (Cosmos and History: The Journal of Natural and Social Philosophy, 2020)
A translation of Anna Longo's "Jugements infinis et logique transcendantale," originally published in Le paradoxe de la finitude (2019). The infinite judgement has long been forgotten and yet, as I am about to demonstrate, it may be urgent to revive it for its critical and productive potential. An infinite judgement is neither analytic nor synthetic; it does not produce logical truths, nor true representations, but it establishes the genetic conditions of real objects and the concepts appropriate to them. It is through infinite judgements that we reach the principle of transcendental logic, in the depths of which all reality can emerge in its material and sensible singularity, making possible all generalization and formal abstraction.